The Effect of Reading Water Ayatul Kursi on The Germination Lettuce Plant (Lactuca sativa L.) (Journal Intellectual Sufism Research (JISR), 2020)
Reading water ayatul kursi is water containing the name Alloh, and the most magnificent verse in the Qur'an. Water can respond to words, images and sounds, so that affect the germination of lettuce plants. The purpose of this study is to describe the number of verses reciting the most optimal for germination of lettuce (Lactuca sativa L.). Amount of reading ayatul kursi in this study are 1, 2, 3, 4 and control. The results of the study showed that the most optimal number of verse recitations was the number of readings as much as 4 times which was 2.28 cm.